Influence of Creative Thinking Beliefs on Sustainable Development Behavior in Higher Education Students. an Approach from the Theory of Planned Behavior [Influencia de Las Creencias del Pensamiento Creativo en el Comportamiento del Desarrollo Sostenible en Alumnos de Educación Superior. Una Aproximación Desde la Teoría del Comportamiento Planificado] - Galleguillos-Cortes, C (Universidad Austral de Chile, 2022)
The purpose of this research has been to determine the influence of creative thinking beliefs on sustainable development behavior in higher education students from the theory of planned behavior. The hypotheses proposed are based on the fact that one’s own belief in the generation of ideas, the influence of the generation of ideas depending on the immediate context of the individual and the capacity of self-efficacy at the moment of generating ideas, predict intention and then, behavior towards sustainable development. 431 students from public and accredited university in Chile have been surveyed, supported by a model of structural equations. The results obtained have partially confirmed the hypotheses as regards attitude and control of perceived behavior, being these significantly and positively related to intention and this in turn, with control of perceived behavior, predict behavior. © 2022. Estudios Pedagogicos. All Rights Reserved.